Intra-articular corrective osteotomy for malunited Hoffa fracture: A case report - Iwai, Takao (BioMed Central, 2012)
Hoffa fracture, an isolated coronal plane fracture of the posterior aspect of the femoral condyle, is known as an unstable, intra-articular fracture, and therefore, operative treatment is recommended. However, insufficient open reduction or failure of fixation may lead to malunion. We performed intra-articular corrective osteotomy for a malunited Hoffa fracture in a 31-year-old man and obtained good functional and radiographic results. This report suggests that intra-articular corrective osteotomy for malunited Hoffa fracture offers a good outcome and should be considered as salvage treatment.